Acetaldehyde-Reinforcing Effects: A Study on Oral Self-Administration Behavior - Peana, Alessandra T.; Muggironi, Giulia; Diana, Marco (Frontiers in Psychiatry, 2010)
Acetaldehyde (ACD) is the first metabolite of ethanol. Although, the role of ACD in ethanol addiction has been controversial, there are data showing a relationship. The objective of the current study was further to test the hypothesis that ACD itself is reinforcing. For this reason, we carried out a study on operant oral ACD self-administration. Wistar rats were trained to self-administer tap water or ACD by nose-poking in daily 30 mins sessions for 15 consecutive days. Response on active nose-poke caused delivery of ACD solution or tap water, whereas responses on inactive nose-poke had no consequences. The results show that ACD maintains oral self-administration behavior and rates of active nose-pokes significantly higher than tap water. The dose-response plot for oral ACD self-administration is a “bell-shaped” curve suggesting reinforcing properties only in a limited range of doses. Furthermore, rats self-administering ACD show a deprivation effect upon ACD removal and gradually reinstated active nose-poke response when ACD was reintroduced. Overall, this study shows that ACD is orally self-administered and further supports the hypothesis that ACD possesses reinforcing properties, which suggests that some of the pharmacological effects attributed to ethanol may result from the its biotransfomation into ACD, thereby supporting an active involvement of ACD in ethanol addiction.